Detection of Leishmania major In Naturally Infected Sand Flies Using Semi Nested-PCR - MA Oshaghi; MR Yaghobi-Ershadi; M Abbassi; P Parvizi; AA Akhavan; A Rahimi Foroshani; AR Zahraei; Y Rassi; F Mohtarami (Tehran University of Medical Sciences, 2008)
"nBackground: The aim of this study was to assess Leishmania infection in sand fly species from areas where leishmaniasis is endemic. This is important for prediction of the risk and expansion of the disease."nMethods: In this cross-sectional study we used a PCR-based method for detection of Leishmania minicircle DNA within individual sand flies from Orzoieh, a new endemic leishmaniasis focus in southern Iran."nResults: We detected minicircle DNA in 6 of 92 (6.5%) Phlebotomus (Phlebotomus) papatasi collected indoor, while all of previous microscopic examination of sand flies specimens was negative for Leishmania promastigotes in the region. The species were identified as Leishmania (Leishmania) major by comparison of PCR products with a L. major positive control. All the Leishmania-positive sand flies were confirmed as P. (P.) papatasi by using a morphological key of Iranian sand flies."nConclusion: Since PCR method is relatively easy and can process a large number of samples, it will be a powerful tool for the rapid identification of Leishmania species as well as monitoring the infection rate in sand fly populations in areas of low endemicity of leishmaniasis.